The Reflective Practitioner: How Professionals Think in Action - Schön, Donald A. (s.l. Basic Books, 1983)
A leading M.I.T. social scientist and consultant examines five professionsengineering, architecture, management, psychotherapy, and town planningto show how professionals really go about solving problems.The best professionals, Donald Schön maintains, know more than they can put into words. To meet the challenges of their work, they rely less on formulas learned in graduate school than on the kind of improvisation learned in practice. This unarticulated, largely unexamined process is the subject of Schöns provocatively original book, an effort to show precisely how reflection-in-action works and how this vital creativity might be fostered in future professionals.